Effect of Capital Structure on Profitability with Liquidity as a Moderating Variable: Empirical Study on Food and Beverage Companies - Yohanes, Yohanes (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study investigates the effect of capital structure on profitability with liquidity as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange during 2019-2023. Using a quantitative approach, this study uses secondary data from 26 companies selected by purposive sampling. Profitability is measured using return on assets, return on equity, and net profit margin, while capital structure and liquidity are represented by debt to equity ratio and current ratio. The study applies panel data regression and moderated regression analysis using Eviews 13. The novelty of this study lies in explicitly integrating liquidity as a moderating variable in the relationship between capital structure and profitability, which has hardly been addressed in previous studies. The findings show that capital structure has a negative effect on return on assets and net profit margin but has a positive effect on return on equity. Liquidity does not significantly moderate the effect of capital structure on return on assets and net profit margin; however, it significantly moderates the relationship with return on equity, indicating that high liquidity may weaken the positive effect of leverage on shareholder returns. This study concludes that capital structure decisions should consider liquidity conditions to ensure sustainable profitability, especially in industries with operating cash flow volatility. Future research is recommended to explore non-linear relationships and use broader financial indicators to strengthen the generalizability of findings across sectors.